STRESSOR FACTORS IN UNDERGRADUATE STUDENTS OF THE ACCOUNTING SCIENCES FACULTY - UNMSM - Gutiérrez Hubby, Ana María (2016)
This article exposes the problem of academic stress in undergraduate students of the Faculty of Accounting Sciences of the UNMSM. It is based on the first results obtained from the study “Academic stress, determination and solution strategies for the Business Economic Area for the University of San Marcos and the University Center de los Lagos”, developed by the author this year, where the possible academic stressors are addressed. The study sample consisted of 353 students from the first and ninth semester of studies. Through a factorial analysis of components, the objective information on the stress levels present in the studied population was determined. The results show that half of the population surveyed present stress, aggravated in 2.8% of the students. Nine stress factors such as “the inability to participate in decisions about their own academic work”, “a lack of control over their own academic performance” and “ students’ academic overload “, were identified as the most recurrent stressors. Likewise, students in the ninth semester concentrate higher levels of stress, and women, in terms of gender distinction.